2021
DOI: 10.3389/fphys.2021.762102
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of Carbon Monoxide-Related Gene Expression in a Deep-Diving Marine Mammal

Abstract: Marine mammals such as northern elephant seals (NES) routinely experience hypoxemia and ischemia-reperfusion events to many tissues during deep dives with no apparent adverse effects. Adaptations to diving include increased antioxidants and elevated oxygen storage capacity associated with high hemoprotein content in blood and muscle. The natural turnover of heme by heme oxygenase enzymes (encoded by HMOX1 and HMOX2) produces endogenous carbon monoxide (CO), which is present at high levels in NES blood and has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 117 publications
0
8
0
Order By: Relevance
“…However, the precise orchestra of protective mechanisms, including antioxidant capacity, might vary with species based on Frontiers in Physiology frontiersin.org their life history traits, with age and with sex. For instance, the muscle expression of several antioxidant genes increased with age and diving ability in northern elephant seals and hooded seals (Vázquez-Medina et al, 2011;Piotrowski et al, 2021) and some antioxidants were observed to be higher in northern elephant females than in males (Piotrowski et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the precise orchestra of protective mechanisms, including antioxidant capacity, might vary with species based on Frontiers in Physiology frontiersin.org their life history traits, with age and with sex. For instance, the muscle expression of several antioxidant genes increased with age and diving ability in northern elephant seals and hooded seals (Vázquez-Medina et al, 2011;Piotrowski et al, 2021) and some antioxidants were observed to be higher in northern elephant females than in males (Piotrowski et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, while HMOX1 expression in skeletal muscle of northern elephant seals is associated with the expression of other antioxidants, correlates with age and was highest in adult females, HMOX2 expression did not vary with age or sex (Piotrowski et al, 2021). Adult females are thought to dive beyond their calculated aerobic dive limit (Hassrick et al, 2007) and thus, the observed elevated expression may be needed to protect them from a more severe risk of oxidative damage (Piotrowski et al, 2021). These results show that the precise interplay of antioxidants may vary with species age and sex.…”
Section: Elevated Antioxidant Gene Expression In Hooded Seal Neuronsmentioning
confidence: 91%
See 1 more Smart Citation
“…To date, extravascular tissue CO has been reported in tissues from healthy rodents and from deceased humans (Vreman et al, 2005;Vreman et al, 2006). Extravascular CO has also been recently reported in skeletal muscle from elephant seals which is over four times as high as that found in similar tissues from the healthy rodents and humans (Piotrowski et al, 2021). While most of the prior research has focused on measuring CO in blood, heme oxygenase proteins in tissues, and expression of heme oxygenase genes in relation to various conditions and treatments, very few studies have investigated the quantity and pattern of distribution of extravascular CO.…”
Section: Introductionmentioning
confidence: 90%
“…The extraction of CO and its quantification in tissues follows previously established methods (Byrne et al, 2022;Piotrowski et al, 2021;Vreman et al, 2005). Briefly, tissues were thawed and rinsed with chilled KH2PO4 buffer (pH 7.4) to remove any remaining excess blood and then placed into microcentrifuge tubes.…”
Section: Quantification Of Co In Tissuesmentioning
confidence: 99%